The Creative Search for an Insight in Account Planning: An Absorptive Capacity Approach. Issue 3 (3rd July 2018) - Parker, John; Ang, Lawrence; Koslow, Scott
Abstract : In advertising agencies, insight is frequently sought to solve advertising problems. However, the ideation process of the account planner is not well understood. Viewing account planning through a lens of absorptive capacity suggests that planning is about identifying and assimilating external information about consumers for use in the creative process. Account planners thus need to search deliberately for insight and work hard to express it to the creatives, who then exploit it to develop powerful creative ideas. The study adopts an in-depth grounded theory investigation of the insight phenomenon among 20 Sydney-based account planners. The findings reveal that identifying and applying insight is a highly creative process. The account planner uses research, personal knowledge domains, challenging conventions, borrowed sources, and central narrative extension to search for insights. However, because not all insights are equal, this study also uncovered what account planners consider quality insight. These include attributes of originality, relatability, usability, and vision. These findings provide guidelines for marketers and account planners who seek insight in framing an advertising message.